2017
DOI: 10.1007/s10897-017-0098-3
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Streamlined Work Flow for Handling Patients’ Genetic Testing Insurance Authorizations

Abstract: Obtaining genetic testing insurance authorizations for patients is a complex, time-involved process often requiring genetic counselor (GC) and physician involvement. In an effort to mitigate this complexity and meet the increasing number of genetic testing insurance authorization requests, GCs formed a novel partnership with an industrial engineer (IE) and a patient services associate (PSA) to develop a streamlined work flow. Eight genetics clinics and five specialty clinics at the University of Michigan were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…answering patient questions daily and never giving exact out-ofpocket costs. The timing of tasks was less variable among respondents, but as previous studies have shown, these data indicated that many tasks are completed outside of direct patient counseling (Attard, Carmany, & Trepanier, 2018;Uhlmann et al, 2017).…”
Section: Discussionmentioning
confidence: 62%
“…answering patient questions daily and never giving exact out-ofpocket costs. The timing of tasks was less variable among respondents, but as previous studies have shown, these data indicated that many tasks are completed outside of direct patient counseling (Attard, Carmany, & Trepanier, 2018;Uhlmann et al, 2017).…”
Section: Discussionmentioning
confidence: 62%
“…36 However, although some genotypephenotype correlations in specific SDHx-related HNPGL are evident, 37 there is a significant clinical overlap of syndromes caused by different SDHx mutations. For this reason, and as genetic testing becomes more accessible and affordable, 38 initial screening for known pathogenic mutations in all 12 of the known hereditary susceptibility genes likely improves sensitivity and patient care in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Delegation to numerous staff positions including personnel to manage insurance authorization (Uhlmann, Schwalm, & Raymond, ), genetic counseling assistants (Pirzadeh‐Miller et al, ), and additional clinical personnel (i.e. non‐genetics professionals) can directly aid in the genetic counseling process (Cohen et al, ; Cohen & McIlvried, ; O'Shea et al, ).…”
Section: Discussionmentioning
confidence: 99%